Germline-mediated ubiquitous recombination in ScxCre male mice: Implications for tendon research - Haiyin Li; Christopher L. Mendias; Chike Cao (PLoS ONE, 2026)
Scleraxis (Scx), a basic helix-loop-helix (bHLH) transcription factor, is a primary marker for tendon and ligament lineages. Accordingly, mouse models utilizing Cre recombinase under the control of the Scx locus provide a powerful tool for conditional gene manipulation in tendon and ligament tissues. The constitutive ScxCre mouse line is widely used for tendon-specific genetic studies. In this study, we show that ScxCre exhibits substantial unintended off-target activity in the male germline, resulting in ubiquitous recombination of floxed alleles in all tissues of the offspring. Transmission of recombined LoxP alleles occurred independently of Cre inheritance, indicating that ScxCre-mediated recombination took place before meiosis in diploid male germ cells. In contrast, this off-target activity was not observed in female germline. These findings highlight a critical need for stringent parental sex selection when using ScxCre lines to ensure tissue-specific targeting and to avoid unintentional global gene deletion or transgene activation.